Aplicação de cobre na cultura da soja em solos com altos teores de fósforo - Cancian, Mateus (2018)
Soils in the state of Rio Grande do Sul were originally well supplied with micronutrients. Thus, at the beginning of the introduction of the soybean crop, micronutrients were not recommended for fertilization. It is only after successive years of extraction of these nutrients by the increasing yields and recurrent applications of phosphate fertilizers over several years and cultures in high doses that a greater frequency has been observed in the occurrence of deficiencies. The availability of micronutrients to the plant is affected by various soil and environmental factors. The objective of this study was to evaluate if the application of Cu, via foliar, in the soybean crop is able to provide increases in grain yield, in cultures conducted in soils with high levels of P. The experiment was conducted from september 2015 to may of 2017, in the municipality of Pinhal Grande in a Typic Hapludalf. The experiment was installed in a randomized complete block design, in a factorial scheme (3x3), with four replications. The treatments were composed of three fertilization doses with P2O5 (0, 69 and 138 kg ha-1) and three Cu doses (0, 10 and 20 g ha-1 Cu), making a total of nine treatments. In the first crop (crop 2015/2016), Cu and P leaf content and productivity were evaluated, and in the second crop (2016/2017 crop) the leaf content of Cu and P was evaluated, nodulation, yield components, productivity and economic analysis. The application of leaf copper and phosphorus positively influenced the number of vegetables per plant, grains per plant, the mass of 1000 grains and the productivity of the soybean crop. The application of copper and phosphorus did not influence the number of grains per legume, number of nodules per plant and mass of nodules. In soils with very high levels of phosphorus and that received applications of high doses of phosphorus there was response to foliar fertilization with copper in the production of soybeans, which was economically feasible. On the other hand, the increments provided by the application of phosphorus in soils with very high contents were not economically viable.